Amyloid-beta metabolism in age-related neurocardiovascular diseases - Aivalioti, Evmorfia; Georgiopoulos, Georgios; Tual-Chalot, Simon; Bampatsias, Dimitrios; Delialis, Dimitrios; Sopova, Kateryna; Drakos, Stavros G; Stellos, Konstantinos; Stamatelopoulos, Kimon (European heart journal, 2025)
Epidemiological evidence suggests the presence of common risk factors for the development and prognosis of both cardio- and cerebrovascular diseases, including stroke, Alzheimer's disease, vascular dementia, heart, and peripheral vascular diseases. Accumulation of harmful blood signals may induce organotypic endothelial dysfunction affecting blood-brain barrier function and vascular health in age-related diseases. Genetic-, age-, lifestyle- or cardiovascular therapy-associated imbalance of amyloid-beta (Aβ) peptide metabolism in the brain and periphery may be the missing link between age-related neurocardiovascular diseases. Genetic polymorphisms of genes related to Aβ metabolism, lifestyle modifications, drugs used in clinical practice, and Aβ-specific treatments may modulate Aβ levels, affecting brain, vascular, and cardiac diseases. This narrative review elaborates on the effects of interventions on Aβ metabolism in the brain, cerebrospinal fluid, blood, and peripheral heart or vascular tissues. Implications for clinical applicability, gaps in knowledge, and future perspectives of Aβ as the link among age-related neurocardiovascular diseases are also discussed.